Educação Profissional no Sistema "S": avaliação dos programas educacionais em Fortaleza-CE - Marinho, Gabrielle Silva (2012)
The paper discusses the evaluation of educational programs developed in vocational education. This is an investigative analysis on the evaluation system developed by the organizations of the System "S" in Fortaleza. The courses taught by "S" System seek to train individuals for the exercise of citizenship and the world of work, contextualized in Brazilian organizations responsible for vocational education. The aim of this study is to analyze the concepts and techniques of evaluation models adopted by the educational system "S" to perform a comparative analysis of models, identifying the approach adopted in the six organizations studied. A specific manner, which proposes to verify institution evaluates the educational programs, describe the professional conducting the assessment, identify the criteria that are used, revealing the processes of assessment, to analyze decision-making, as well as the actions take effect after the result of evaluation. The nature of applied research with qualitative and quantitative descriptive approach, begins with bibliographical and documentary research, technical procedure takes as a case study, by comparing and uses as an instrument for data collection the questionnaire, with characterization of the respondents and their opinions in scale. Search information in the exploratory phase of research with the purpose of ascertaining whether the six organizations follow the rules inherent in professional education in the country, consider whether the modularization of the shares and if the formation process focuses on professional qualifications, and, how is the insertion of forming in the labor market. The study notes that there are differences between the models of evaluation of programs implemented, the academic profile of evaluators System "S", considering that the professionals have training graduates, postgraduates and specialists in various fields of knowledge with a predominance of education. The analysis of the criteria, techniques and evaluation procedures used by educational units through the pedagogical project of each subsystem, when confronted with the theoretical evidence that the assessment of educational practices in the System "S" is based on valuation models and theoretical empirically related to decision making, and with the concepts of educational evaluation prescribed in contemporary literature. Moreover, they are sustained on policies and procedures for the development of education and training, besides enabling the insertion and rise to the labor market.